Identification Of Potential Hazards Using The Hazard Identification Risk Assessment And Risk Control (HIRARC) Method, Case Study: PT. X - Yunita, Yosi; Ekayuliana, Arifia; Wijayanti, Fitri (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
PT. X is a company producing 3 kg LPG gas. The absence of a good OHS system and the many cases of work accidents are problems that must be resolved. Therefore, this research aims to identify potential hazards in the production area, assess risks, and implement risk control using the HIRARC method based on the Australian Standard/New Zealand Standard for Risk Management 13 scale (AS/NZS 4360). The type of research used is descriptive qualitative. The results of this study show that there are 13 potential hazards, 11 low risk categories, 3 medium risk categories, and 2 high risk categories. The form of control that can be done by applying good and correct PPE, changing manual conveyor equipment to automatic conveyors and providing google forms to determine worker readiness. PT. X merupakan perusahaan yang memproduksi gas elpiji 3 kg. Belum terdapatnya sistem K3 dengan baik serta banyaknya kasus kecelakaan kerja menjadi suatu masalah yang harus diselesaikan. Oleh sebab itu penelitian ini memiliki tujuan guna melakukan identifikasi terhadap potensi bahaya yang ada di area produksi, mengukur risiko, serta menerapkan pengendalian risiko mempergunakan metode HIRARC berdasarkan skala Australian Standard/New Zealand Standard for Risk Management 13 (AS/NZS 4360). Jenis penelitian yang dipergunakan yakni deskriptif kualitatif. Temuan penelitian ini menunjukan ada 13 potensi bahaya, 11 kategori low risk, 3 kategori medium risk, serta 2 kategori high risk. Bentuk pengendalian yang mampu dilakukan dengan penerapan APD yang baik dan benar, pergantian peralatan conveyor manual menjadi conveyor otomatis dan memberikan google formulir untuk mengetahui kesiapan pekerja.